FORMULATION AND IN VITRO EVALUATION OF PIROXICAM EMULGEL (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
The present work is concerned with the formulation and evaluation of Piroxicam emulgel employing carbopol 934 and xanthan gum as polymers. The emulgel is prepared by combining the gel and emulsion. The gel in formulations were prepared by dispersing Carbopol 934 and xanthan gum separately in purified water with constant stirring at a moderate speed and then the pH was adjusted to 4 to 5.4 using Tri-ethanol amine (TEA). The oil phase in the emulsion consists of oleic acid and span-80. The aqueous phase in the emulsion was prepared using Tween-80, propylene glycol and distilled water. The prepared emulgel formulations were subjected to evaluation studies like Physical appearance, rheological studies, estimation of drug content and in-vitro drug release. The appearance of prepared emulgel was white. The pH of the emulgel was found to be 5.4. The in vitro drug release studies revealed that formulation F1 showed 85.20% and formulation F2 showed 79.23% of drug release at the end of 8 hrs. The drug release of F1 formulation follows zero order kinetics.